A Study on Reproductive Morbidity and Menstrual Hygiene Among Adolescent Girls of Urban Slum Area of Chitradurga - Ramya V; Mayuri Reddy Reddy; Sridevi BK (Medsci Publications, 2016)
Introduction: A large number of Adolescents in India are out of school, get married early, work in vulnerable situations, sexually active and are exposed to peer pressure. This study was conducted among adolescent girls with the objective to assess their menstrual problems, health seeking behavior and practices during menstruation. Methods: A Community based cross sectional observational study was conducted among 490 late adolescent girls (15-19 years) in the urban field practice area of Chitradurga. Results: The mean age at menarche, marriage and pregnancy among subjects was 13.54+ 1.0 years, 17.5 ± 1.29 years and 18.23 + 0.9 years respectively. The most common reproductive health problems were dysmenorrhoea (37.1%) and menstrual irregularities (18.6%). Only 23.89% adolescent girls having reproductive health morbidities sought health. Majority (83.92%) of adolescent girls were using sanitary pads during menstruation. There was statistically significant association between the type of menstrual absorbent material used and educational status of girls, educational status of their mothers and socio economic status. Conclusion: The problems of adolescent girls like early marriage, school dropout and teenage pregnancy are still prevalent in the community. Health care seeking behavior during period of reproductive illness was found to be very poor.